Activity and stability of immobilized Candida rugosa lipase on chitosan coated Fe3O4 nanoparticles in aqueous and organic media - Abd-Elhakeem, Mohamed A.; Elsayed, Ahmed M.; Alkhulaqi, Taher A. (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Fe3O4 (magnetite) nanoparticles were prepared by coprecipitation method, coated by chitosan and functionalized by glutaraldehyde. Lipase enzyme from Candida rugosa was immobilized on the prepared particles via cross linking reaction. Synthesis steps and characterization were examined by XRD, TEM, and FTIR. The immobilization conditions were 10 mL of phosphate buffer (0.1 M, pH 6.5) containing 30 mg of functionalized magnetic chitosan nanoparticles and 2.0 mg·mL-1 of lipase, immobilization temperature of 4 ℃ and immobilization time of 1 h. Under these conditions, lipase was successfully immobilized with loading capacity of 87 mg/g. The immobilized enzyme showed good operational and storage stability, where it remained stable after 30 days of storage at 4◦C.and retained about 61% of its initial activity after twenty repeated uses. Finally enzymatic catalyze synthesis of butyl and hexyl oleate at 40 ◦C with shaking (200 rpm) was realized in n-hexane and confirmed by GC analysis.